Innovative Financial Instruments for Climate Action: Challenges and Opportunities of Debt for Climate Swaps in Latin America - Alonso, José Fernández (2025)
Sovereign debt crisis and accelerating climate change have emerged as deeply interconnected global challenges. The fiscal impact of the COVID-19 pandemic and the economic fallout from the Ukraine war have pushed public debt to historic highs, while the frequency and severity of climate disasters continue to intensify. These converging crises disproportionately affect developing countries, spurring renewed attention to debt-for-climate action swaps as a potential policy solution. This article presents a comprehensive analysis of such debt swap mechanisms, drawing on an original dataset spanning from their inception in the late 1980s to present-day initiatives. We focus particularly on Latin America, a region that offers valuable insights given its extensive experience with both sovereign debt crises and debt-for-nature swaps, coupled with its high vulnerability to climate change impacts.